Efficient operator method for modeling mode mixing in misaligned optical cavities - Hughes, W; Doherty, T; Blackmore, J; Horak, P; Goodwin, J (American Physical Society, 2024)
The transverse field structure and diffraction loss of the resonant modes of Fabry-Pérot optical cavities are acutely sensitive to the alignment and shape of the mirror substrates. We develop extensions to the mode-mixing method applicable to arbitrary mirror shapes, which both facilitate fast calculation of the modes of cavities with transversely misaligned mirrors and enable the determination and transformation of the geometric properties of these modes. We show how these methods extend previous capabilities by including the practically motivated case of transverse mirror misalignment, presenting the ability to study the rich and complex structure of the resonant modes.